Anthropometric Mobility During Childhood - Daniel L. Millimet; Rusty Tchernis (Institute for the Study of Labor (IZA), 2013)
While childhood obesity has become a significant public health concern over the last few decades, knowledge concerning the origins of or persistence in childhood anthropometric measures is incomplete. Here, we utilize several nonparametric measures of mobility to assess the evolution of weight, height, and body mass index during early childhood. We find that mobility is quite high prior to primary school and then declines noticeably. However, there are important sources of heterogeneity, including race, gender, and age, that should prove insightful to researchers and policymakers.
Keywords: C23; I12; I18; 330; childhood obesity; persistence; mobility